Preparation of a novel composite phase change material (PCM) and its locally enhanced heat transfer for power battery module. (15th January 2019) - Zou, Deqiu; Liu, Xiaoshi; He, Ruijun; Zhu, SiXian; Bao, Jiaming; Guo, Jiangrong; Hu, Zhigang; Wang, Binghui
Graphical abstract: Highlights: Locally enhanced heat transfer for power battery module was presented. A novel CPCM was prepared by loading graphene, carbon tube and expanded graphite into paraffin. The locally enhanced heat transfer effect of the CPCM was almost the same as copper foam/PCM. Temperature of the battery module was more uniform when the enhanced region was narrowed. Abstract: The rapid development of new energy vehicles urgently requires lightweight power battery modules with excellent thermal performance. To achieve this goal, a high thermal conductivity composite phase change materials (CPCM) was prepared and its locally enhanced heat transfer characteristics of power battery module were experimentally studied. The results showed that CPCM had almost the same localized heat transfer effect as copper foam/PCM under different thermal environment. Furthermore, locally enhanced heat transfer characteristics have been comparatively studied for center regions with different sizes in the power battery module using the CPCM as cooling media. The results showed that when 4 batteries were enhanced using CPCM, the maximum temperature in a 36-battery module during the 3C discharge was limited to 44.6 °C while the maximum temperature difference was limited to 0.8 °C. Interestingly, the results revealed that the maximum temperature of battery module was slightly increased (less than 1%) but the temperature difference was reduced by 46.7% compared with enhancement for 16 batteries, which was helpful to improve the temperature consistency of the battery module.